Influenza Vaccination Among Patients with Noncommunicable Diseases: A Survey About Awareness, Usage, and Unmet Needs in the Czech Republic - Zdeněk Zadražil; Lenka Cesneková; Jan Kynčl; Zuzana Krištúfková; Laura Colombo; Sanjay Hadigal (Drugs - Real World Outcomes)
Abstract Background People with noncommunicable diseases (NCDs) are at a higher risk of contracting vaccine-preventable diseases, such as influenza, with a higher likelihood of severity and complications. However, the immunization rates for the influenza vaccine among this population in the Czech Republic are very low. Objective This survey, among adults with NCDs in the Czech Republic, assessed the knowledge, attitudes, and gaps toward vaccination in general and influenza vaccination in particular. Methods The survey was conducted between February 2023 and March 2023 among patients with NCDs in the Czech Republic. A structured web-based questionnaire with open-ended questions was administered. This study is a preplanned subgroup ancillary analysis of a previous multicentric study conducted on 1106 patients. Results In all, 120 patients were enrolled, with 62% (74) aged between 41 and 60 years. Approximately 30% (36) had taken the influenza vaccine in the last 2 years and 70% (84) had not. Of the total sample, only 46% (55) had a positive opinion about influenza vaccines; this increased to 91% (33) among those vaccinated against the influenza virus. The main drivers of influenza vaccination were general physician (GP) recommendation [50% (18)] and patient initiative [47% (17)]. The main barriers to the influenza vaccine were lack of belief regarding its need [52% (44)], experience of mild severity of influenza [30% (25)], and lack of GP recommendation [25% (21)]. Physicians, dedicated websites, and family members are the most common sources of information regarding influenza. Even among those vaccinated for influenza, only 17% (6) had information about the risk of not taking the vaccine. A high level of dissatisfaction with the information was found among patients not vaccinated against influenza. People wanted more information on who should not receive the influenza vaccination. Unvaccinated patients sought information on side effects and efficacy. Only 40% (48) of the respondents said that they are likely/extremely likely to take an influenza vaccination in the future. Conclusions Healthcare practitioners are the key influencers for people to get vaccinated. The dissemination of information about the importance of influenza vaccines for people with NCDs needs to be increased in the Czech Republic.